2023
DOI: 10.1002/bbb.2472
|View full text |Cite
|
Sign up to set email alerts
|

Potential biofuel exploitation from two common Vietnamese Euphorbia plants (Euphorbiaceae)

Abstract: In this work, two common Vietnamese Euphorbia plants, Euphorbia tirucalli Linn. (the milk bush) and Euphorbia tithymaloides Linn. (the milk hedge), have been investigated for potential use as biofuels. Their aerial parts were macerated with different solvents [petroleum ether, ethyl acetate (EA), methanol and water] to obtain extracts. The extracts were put through petrochemical composition analyses, including elemental analysis, Fourier transform infrared spectra recording and fatty acids composition analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Euphorbia, belonging to the family Euphorbiaceae, comprises about 2000 species and is one of the largest flowering plant genera in the world 1 . Many fuel plants have been reported in this genus, providing biomass for the production of biocrude, bioethanol and other bioenergy resources [2][3][4][5] . Euphorbia tirucalli (2n = 2x = 20) 6 , commonly referred to as milk bush, pencil cactus, pencil tree, or naked lady, is an evergreen shrub or small tree with typically succulent branched stems and small non-succulent leaves (Fig.…”
Section: Background and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Euphorbia, belonging to the family Euphorbiaceae, comprises about 2000 species and is one of the largest flowering plant genera in the world 1 . Many fuel plants have been reported in this genus, providing biomass for the production of biocrude, bioethanol and other bioenergy resources [2][3][4][5] . Euphorbia tirucalli (2n = 2x = 20) 6 , commonly referred to as milk bush, pencil cactus, pencil tree, or naked lady, is an evergreen shrub or small tree with typically succulent branched stems and small non-succulent leaves (Fig.…”
Section: Background and Summarymentioning
confidence: 99%
“…It exudes a milky latex from the wounded shoots or leaf stems 3,8 . Recent studies demonstrated that the compounds in the latex exhibit high petrochemical properties 5,9,10 . In addition, this species has important medicinal value, with its latex being traditionally used for the treatment of cancer, asthma, arthritis, rheumatism and so on [11][12][13][14] .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation